Methods of weaning preterm babies <30 weeks gestation off CPAP: a multicentre randomised controlled trial. Issue 4 (18th May 2012) - Todd, David A; Wright, A; Broom, M; Chauhan, M; Meskell, S; Cameron, C; Perdomi, A M; Rochefort, M; Jardine, L; Stewart, A; Shadbolt, B
Abstract : Background: Controversy exists whether different continuous positive airway pressure (CPAP) weaning methods influence time to wean off CPAP, CPAP duration, oxygen duration, Bronchopulmonary Dysplasia (BPD) or length of admission. Aims: In a multicentre randomised controlled trial, the authors have primarily compared CPAP weaning methods impact on time to wean off CPAP and CPAP duration and secondarily their effect on oxygen duration, BPD and time of admission. Methods: Between April 2006 and October 2009, 177 infants <30 weeks gestational age (GA) who fulfilled stability criteria on CPAP were randomised to one of the three CPAP weaning methods (M). M1: Taken 'OFF' CPAP with the view to stay 'OFF'. m 2 : Cycled on and off CPAP with incremental time 'OFF'. M3: As with m 2, cycled on and off CPAP but during 'OFF' periods were supported by 2 mm nasal cannula at a flow of 0.5 l/min. Results: Based on intention to treat analysis, there was no significant difference in mean GA or birthweight between the groups (27.1±1.4, 26.9±1.6 and 27.3±1.5 (weeks±1SD) and 988±247, 987±249 and 1015±257 (grams±1SD), respectively). Primary outcomes showed M1 produced a significantly shorter time to wean from CPAP (11.3±0.8, 16.8±1.0, 19.4±1.3 (days±1SE) p<0.0001, respectively) and CPAP duration (24.4±0.1, 38.6±0.1, 30.5±0.1 (days±1SE) p<0.0001, respectively). All the secondary outcomes were significantly shorter with M1, (oxygen duration: 24.1±1.5, 45.8±2.2, 34.1±2.0 (days±1SE) p<0.0001, BPD: 7/56 (12.5%), 29/69 (42%), 10/52 (19%) p=0.011 and length of admission: 58.5±0.1, 73.8±0.1 69.5±0.1 (days±1SE) p<0.0001, respectively). Conclusion: Method 1 significantly shortens CPAP weaning time, CPAP duration, oxygen duration, BPD and admission time.